CULTURE AND INTERCULTURALITY IN THE PERUVIAN REALITY PROCESS: A LOOK FROM THE LITERATURE - Campos-Pérez, Rosalvina (2020)
This research was developed to investigate how literary discourse rightly contributes to the knowledge of reality and allows the readers to develop their ideas about the context surrounding them or the production of artistic texts. It established the confi guration of culture and interculturality, the artistic contributions of the poetry of the Generation of 50 in the process of Peruvian reality from the perspective of literature through a critical and refl exive reading of theoretical texts, critical texts (metatexts), and artistic texts (the poetry of the Generation of 50). In this way, we see that literature becomes a means of artistic expression to display the author's intercultural competence and the interpretative capacity of the reader. Keywords: artistic expression – context – poetry – literary discourse